Metabolic status and genetic features of one-carbon metabolism in psoriasis patients during antimetabolite-based therapy - K.V. Misiura; L.V. Roschenyuk; T.V. Tyzhnenko; V.M. Vorontsov; P.P. Ryzhko; N.H. Puzik; T.E. Tkachyk; O.M. Fedota (Mìžnarodnij Endokrinologìčnij Žurnal)
Background. The purpose was to evaluate the metabolic status of patients with psoriasis depending on the genotype of single-nucleotide polymorphisms (SNP) C677T and A1298C of the MTHFR gene with methotrexate treatment. Materials and methods. 77 patients with psoriasis were included in the study. Their genotypes based on polymorphic variants of the MTHFR gene were determined by the PCR-RFLP. Biochemical indicators were evaluated before and after treatment with methotrexate. Correspondence to the law of normal distribution was verified before further statistical analysis using the T-test, Kolmogorov-Smirnov, Shapiro-Wilk, Wilcoxon tests; Pearson correlation coefficients were calculated. Results. The difference between ALT levels before (0.60 ± 0.04) and after (0.74 ± 0.06) treatment in patients with CT genotype for SNP C677T of the MTHFR gene who received methotrexate is significant (p < 0.008), while in those with CC and TT genotypes, no significant difference was noted. No significant difference was found between AST levels before and after methotrexate treatment in patients with all genotypes — CC, CT and TT. Also, in participants with CT genotype for C677T MTHFR, a significant increase in bilirubin, creatinine, urea was noted after treatment with methotrexate. Carriers of genotype TT on C677T polymorphism of the MTHFR gene after treatment with methotrexate also showed a significant increase in bilirubin, creatinine, α-amylase, urea. In patients with the AA genotype for A1298C polymorphism of the MTHFR gene, the level of all serum biochemical indicators after methotrexate therapy changed significantly (p < 0.05–0.001): α-amylase and total protein decreased, and the levels of other indicators increased. Our study demonstrated that AA genotype on MTHFR A1298C is associated with elevated level of ALT after methotrexate treatment — by almost 1.3 times. No significant changes in any of the indicators were observed in patients with AC genotype after treatment. An analysis was carried out of the relationship between pathological enlargement of the liver — hepatomegaly, diffuse liver diseases and genotypes for SNP C677T and A1298C MTHFR in patients with psoriasis. A negative correlation was found between the number of polymorphic alleles in the patient’s genotype and hepatomegaly (r = –0.91, p = 0.009). The highest increase (14.50 ± 5.37 mm) in the size of the liver is observed in patients with the CCAA genotype, which is prognostically most favorable for the development of psoriasis and its complications. The smallest enlargement of the liver (6.40 ± 2.44 mm) was found in patients with the TTAA genotype, which is a risk factor for the development of psoriasis and side effects during methotrexate therapy. Both single-locus and haplotype analysis suggest that the MTHFR gene polymorphism has an effect during methotrexate therapy in psoriasis patients. It is important to predict the results of pharmacotherapy taking into account personal molecular genetic markers. Conclusions. Assessment of the condition of the liver after treatment with methotrexate showed an inverse relation between an increase in its size and the presence of polymorphic alleles in the patients’ genotype. The highest increase in liver size is observed in patients with the CCAA genotype. Probably, the genotype, in particular CC, allows taking methotrexate for a certain time without significant complications, which affects the condition and characteristics of the liver over time.